The impact of PBD (plant-based diet) on atherosclerosis biomarkers in the risk and progression of coronary heart disease: A systematic review of randomized controlled trials - Shafrina, Amara Azka; Hakiki, Riski; Sari, Raudhah; Ramadhani, Yasmin Nabila; Nauval, Iflan (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2025)
ABSTRACTBackground: Coronary heart disease (CHD) is a leading cause of premature death globally. Plant-based diet (PBD), which emphasizes vegetables, fruits, legumes, grains, oils, and nuts with minimal animal products, is gaining attention for its potential cardiovascular benefits. It may impact atherosclerosis progression by improving lipid profiles, inflammation, blood pressure, and endothelial function.Objective: This review evaluates the effects of PBD on atherosclerosis biomarkers in at-risk individuals and CHD patients.Methods: A systematic review of randomized controlled trials (RCTs) published between 2019 and 2024 was conducted using keywords: "Plant based diet” OR “Mediterranean diet” OR “Vegan diet” OR “Diet” AND “Atherosclerosis”. Studies included were focused on the impact of PBD on blood lipid profile, inflammatory markers, measurements of atherosclerosis progression, anthropometrics, and blood pressure in populations with or without CHD. Databases searched included Cochrane, ScienceDirect, PubMed, Scopus, ProQuest, JSTOR, and ACM.Results: Sixteen out of 2960 studies were reviewed, involving 5,408 participants with interventions ranging from 4 weeks to 7 years. PBD was found to significantly improve lipid profiles by lowering total cholesterol, low-density lipoprotein (LDL), and triglycerides. PBD also reduced inflammatory markers (C-reactive protein (CRP), interleukins), improved endothelial function, and arterial stiffness measurements. It also reduces body weight, waist circumference, and blood pressure. This review highlights the potential of PBD to mitigate cardiovascular risk through improvements in lipid metabolism, inflammation, and endothelial function. While some outcomes varied, evidence supports the incorporation of PBD as a strategy to slow the progression of atherosclerosis to improve cardiovascular health.Conclusion: PBD was found to improve atherosclerosis biomarkers in at-risk individuals and CHD patients by reducing inflammation and improving lipid profiles. Future studies should further explore these relationships, especially on arterial stiffness with larger populations and homogenous sample sizes to establish robust conclusions.Keywords: Atherosclerosis progression; blood lipid profile; coronary heart disease; inflammatory markers; plant-based diet